A composite sandwich plate with a novel core design. (1st June 2018) - Uzal, Anil; Sonmez, Fazil O.; Oz, Fatih E.; Cinar, Kenan; Ersoy, Nuri
Abstract: In this study, a new core design is introduced for sandwich composite structures. Its strength and failure behavior are investigated via three-point bending tests. E-glass-fiber-reinforced epoxy resin is selected as the material for both the core and the face sheets. The core has an egg-crate shape. Acoustic emission (AE) method is used to detect the progression of damage. Signals due to elastic waves caused by activated damage mechanisms are investigated in order to identify the corresponding failure modes. A finite element model of the sandwich structure is developed to predict the failure behavior of the specimens under the loading conditions in the tests. A promising agreement between the results of the finite element model and the experiments is observed. The force-deflection-relation, the failure load as well as the region where damage initiates are accurately predicted.